Samuelson on populist democracy, fascist capitalism, and the vicissitudes of South American economic development (1948-1997) - Mauro Boianovsky (Duke University, Center for the History of Political Economy (CHOPE), 2019)
Paul Samuelson was attracted to the economic dynamics of South American countries because of the links between economic performance and political factors. He discussed the influence of 'populist democracy' on Argentina's relative stagnation, which, he argued in the 1970s and early 1980s, served as a dangerous paradigm for the American economy under stagflation. Moreover, he applied his concept of "capitalist fascism" to deal with military dictatorships in Brazil and (especially) in Chile. The Brazilian translation of his Economics in 1973 brought about a correspondence with Brazilian economists about the "fascist" features of the regime. The main variable behind the South American economic and political processes discussed by Samuelson was inequality, which became also a feature of the American economy since the adoption of market-based policies in the 1980s and after.
Keywords: B22; O11; 330; Samuelson; populism; capitalist fascism; South America; economic development; inequality